The epidemiology of musculoskeletal morbidity in elite rugby union - Davies, M (2017)
Over 7 million participants play rugby union throughout over 120 countries. Despite this global status, very little is known about the longer-term health outcomes of players, or how health and health-related quality of life are influenced by participation in rugby union. The aim of this thesis was to design and undertake an epidemiological study to assess overall health, the presence of morbidity, and development of osteoarthritis within former elite rugby players. In addition to establishing a study, and assessing health and morbidity, secondary aims were to compare the prevalence of morbidity in this population with age-matched representative population-based survey participants, and to examine risk factors associated with the development of osteoarthritis in this population. A cross-sectional questionnaire study was designed to assess physician-diagnosed morbidity, playing exposure, injury history and current health status. Former rugby players for Oxford and Cambridge Universities, and members of the England Rugby Internationals Club, were invited to participate in this study. Data from the English Longitudinal Study of Ageing (ELSA) and the Health Survey for England (HSE) were used as population-based representative comparator groups. These four studies examine the feasibility of involving rugby players in sport-related healthcare research, the prevalence of morbidity and health-related quality of life relative to the general population, the prevalence and risk factors for osteoarthritis-related outcomes, and finally develop a prediction model of end-stage hip failure in this population. Involving players throughout the research cycle as experts of their own experience was seen to influence the research process and questionnaire development, and ensured this process was grounded in players’ beliefs and experiences. In terms of physician-diagnosed morbidity, former players were seen to demonstrate less diabetes than ELSA participants, but more osteoporosis, anxiety, osteoarthritis (OA) and joint replacement. Risk factors for osteoarthritis-related outcomes were seen to vary between the knee, hip and shoulder, and between the definitions of osteoarthritis used (NHANES pain, physician-diagnosed OA or joint replacement). Joint-specific injury was most highly associated with osteoarthritis across all joints and definitions used. The prediction model for hip replacement was strong (AUC 0.88), despite the relatively small development dataset, and again emphasised injury, in addition to Slipped Upper Femoral Epiphysis, age, family history, and playing in the second row, as predictive of hip replacement. This was not externally validated, however internal validation was undertaken. This work has not only established health outcomes in this population, and developed the methodology and survey tools to replicate this work in other cohorts, but also assesses risk factors and strongly predicts poor OA outcome in this population. This work presents potential intervention opportunities for the sport to begin to address the now quantified health deficits; and also presents benefits of elite contact sports participation. These findings should support efforts to ensure healthy participation and adequate proactive management of health at the elite level, for all players.